Writing Puerto Rico Our Decolonial Moment - Rebollo Gil, Guillermo (New Caribbean Studies, 2018)
This book is a manifesto-like consideration of the potentialities of radical political thought and action in contemporary Puerto Rico. Framed within the context of the present economic crisis, of austerity measures, PROMESA and mass migration, this book engages recent literary, artistic and activist work on the island in order to highlight the manners in which such work-however precarious, innocuous and/or fleeting-fosters hope among audiences, artists, protesters and onlookers alike for a more egalitarian and just society. Autoethnographically grounded, informal in tone, and with an eye toward intersectionality, this book serves as a unique contribution to the field of Puerto Rican Studies, by offering alternate points of departure for emergent theorizing and intellectual production across academic disciplines.